Later flowering is associated with a compressed flowering season and reduced reproductive output in an early season floral resource. Issue 6 (4th October 2015) - Rafferty, Nicole E.; Bertelsen, C. David; Bronstein, Judith L.
Abstract : Climate change‐induced shifts in flowering phenology can expose plants to novel biotic and abiotic environments, potentially leading to decreased temporal overlap with pollinators and exposure to conditions that negatively affect fruit and seed set. We explored the relationship between flowering phenology and reproductive output in the common shrub pointleaf manzanita Arctostaphylos pungens in a lower montane habitat in southeastern Arizona, USA. Contrary to the pattern of progressively earlier flowering observed in many species, long‐term records show that A. pungens flowering onset is shifting later and the flowering season is being compressed. This species can thus provide unusual insight into the effects of altered phenology. To determine the consequences of among‐ and within‐plant variation in flowering time, we documented individual flowering schedules and followed the fates of flowers on over 50 plants throughout two seasons (2012 and 2013). We also measured visitation rates by potential pollinators in 2012, as well as both fruit mass and seeds per fruit of flowers produced at different times. Fruit set was positively related to visitation rate but declined with later dates of flower production in both years. Total fruit production per plant was positively influenced by flowering duration, which declined with later flowering onset, as did fruit mass. Individual flowering schedules were consistent between years, suggesting that plants that begin flowering late have lower reproductive output each year. These patterns suggest that if pointleaf manzanita flowering continues to shift later, its flowering season may continue to become shorter, compressing floral resource availability for pollinators and leading to reduced reproductive output. These results reveal the negative effects of delayed phenology on reproductive output in a long‐lived plant. They highlight the value of using natural variation in flowering time, in combination with long‐term data, to anticipate the consequences of phenological shifts.